2021
DOI: 10.1002/htj.22201
|View full text |Cite
|
Sign up to set email alerts
|

Thermal characteristics of forced convection in combined pressure and shear‐driven flow of a non‐Newtonian third‐grade fluid through parallel plates

Abstract: Heat transfer in a non-Newtonian third-grade fluid, flowing under the action of pressure gradient and shear, through two parallel plates, is considered. The upper plate moves with a constant velocity. Constant wall heat fluxes are applied to the plates. Effect of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Muzychka and Edge 25 developed an elegant model for power-law liquids based on the Rabinowitsch-Mooney formulation and computed volumetric flow rates in a variety of ducts including circular and elliptic tubes, parallel channels, rectangular ducts, isosceles triangular ducts, circular annular, and polygonal ducts. Other relevant studies include Chaudhuri et al 26 (on forced convection heat transfer in third-grade viscoelastic fluids in ducts) and Rajagopal and Na 27 (third grade fluids with thermal buoyancy effects in ducts). All these studies confirmed the significant deviation in heat and momentum characteristics due to non-Newtonian behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Muzychka and Edge 25 developed an elegant model for power-law liquids based on the Rabinowitsch-Mooney formulation and computed volumetric flow rates in a variety of ducts including circular and elliptic tubes, parallel channels, rectangular ducts, isosceles triangular ducts, circular annular, and polygonal ducts. Other relevant studies include Chaudhuri et al 26 (on forced convection heat transfer in third-grade viscoelastic fluids in ducts) and Rajagopal and Na 27 (third grade fluids with thermal buoyancy effects in ducts). All these studies confirmed the significant deviation in heat and momentum characteristics due to non-Newtonian behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For integral type liquid, Cauchy stress is computed through integration of general deformation slope. In the case of rate‐type liquids, stress has a relationship with its higher‐order time derivative 8 . Materials having the features of elasticity as well as viscosity under going deformation are termed as “Maxwell fluids.” 9 Though, in 1867, J. C. Maxwell proposed such type of fluid but after only some years, it became popular due to J. G. Oldroyd.…”
Section: Introductionmentioning
confidence: 99%